EFIKASI DIRI, ENGAGEMENT DAN KEMAMPUAN Memperjelas pengaruh kinerja frontliner terhadap kepuasan nasabah bank BCA - Herawati, Heny (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study aims to determine the effect of frontliner performance on customer satisfaction at a private bank in Jakarta through self-efficacy, engagement, and the ability of frontliners. By using descriptive quantitative method. through proportional random sampling. The data was processed using the Structural Equation Model (SEM) with the AMOS 24 application. With a sample of 212 people, the results showed that self-efficacy, engagement and ability had a positive and significant effect on performance. The higher and professional the self-efficacy, engagement, and ability of the banking frontliners, the higher the performance of the bank's employees. And the higher the performance of the frontliners, the more satisfied banking customers will be in receiving the services provided.